Foundation Web Design with Dreamweaver 8 - Grannell, Craig (Apress : Imprint: Apress, 2006)
Dreamweaver is Macromedia's bestselling web design/development environment. Dreamweaver has the capability to generate dynamic website code using server-side languages like ASP, PHP, and ASP.NET. We know that you don't always require a full database-driven site though, so this book focuses on using version 8 of Dreamweaver to design and create usable, standards-compliant websites using XHTML and CSS. One of the highlights of this version is much closer, tighter CSS/XHTML. This book will show you how to make the most of that feature. After a brief introduction to the latest version of Dreamweaver, and how CSS and XHTML fit into it, Craig Grannell looks at using the software for your web design projects in a hands-on, task based manner.